2023
DOI: 10.21203/rs.3.rs-2715241/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How hospitals response to disasters; a conceptual deep reinforcement learning approach

Abstract: During a disaster the requests for using ambulance services increases. Efficient assignment of the ambulances leads to lowering the patients' travel time. Simulating these environments is very complex and needs a solid framework. This paper uses a Deep Reinforcement Learning approach to better schedule ambulance dispatch problem during those disasters. The concept of a call and assignment of ambulances are illustrated and the elements of states, rewards, and actions in the formulations are described. The algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Lee et al developed a multi agent control system based on classic physics model know as spring-mass-damper model. This study revealed that multi agent approach suits well not only for advanced machine learning based models, but also in dealing with conventional and classic models [23].…”
Section: Multi-agent Systemmentioning
confidence: 90%
“…Lee et al developed a multi agent control system based on classic physics model know as spring-mass-damper model. This study revealed that multi agent approach suits well not only for advanced machine learning based models, but also in dealing with conventional and classic models [23].…”
Section: Multi-agent Systemmentioning
confidence: 90%
“…A combination of Transportation Engineering-based policies with conceptual deep reinforcement learning has been used by Mirbakhsh et al to optimize ambulance dispatch in a pandemic or natural disaster circumstances [2]. Dresner et al divided the intersection area into an n×n grid of reservation tiles.…”
Section: Literature Reviewmentioning
confidence: 99%